If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(6 + -1x) + 3x + 6 = 6x + 2 2x + (6 * -1 + -1x * -1) + 3x + 6 = 6x + 2 2x + (-6 + 1x) + 3x + 6 = 6x + 2 Reorder the terms: -6 + 6 + 2x + 1x + 3x = 6x + 2 Combine like terms: -6 + 6 = 0 0 + 2x + 1x + 3x = 6x + 2 2x + 1x + 3x = 6x + 2 Combine like terms: 2x + 1x = 3x 3x + 3x = 6x + 2 Combine like terms: 3x + 3x = 6x 6x = 6x + 2 Reorder the terms: 6x = 2 + 6x Add '-6x' to each side of the equation. 6x + -6x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 0 = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 0 = 2 + 0 0 = 2 Solving 0 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5+12=3+56 | | 3.3q-1.1-4.5q=-0.2q-1.1 | | 4(2x+4)-2(x-4)=3x+60+x | | 4m^2+4m=3 | | X^4+x^2+2=0 | | 7w+2=8w-1 | | 8x+4+5x+8=12x+4 | | 3(13-2)=-3+a | | 2w^2-18=0 | | 5x+37=12x-33 | | 5x-13=8-2xu | | 7x-12=4x+3 | | x^2+4=6x | | 4m^2+4m-3=0 | | 4(x-3)=-20 | | 3b^2-15b=0 | | (x+5)(x-5)=39 | | 2b^3-50b=0 | | b^2-25b=0 | | 2x^2+6x-2=0 | | -1.3+-3.8= | | 5x+3-2x=x-15 | | -2x-x+6=4x+34 | | 5x+3-2=x-15 | | x+(x+5)=25 | | x+(x+5)=63 | | 3c(8*9)=12 | | 33-5x=4x+22 | | 12-10x=217-45x | | 37-y=23+y | | 3y(y+2-15)=0 | | 3x+13=-37-7x |